2015
DOI: 10.1021/nn5064634
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Cell-Culture Platform for Aligned Cell Sheet Monitoring, Transfer Printing, and Therapy

Abstract: While several functional platforms for cell culturing have been proposed for cell sheet engineering, a soft integrated system enabling in vitro physiological monitoring of aligned cells prior to their in vivo applications in tissue regeneration has not been reported. Here, we present a multifunctional, soft cell-culture platform equipped with ultrathin stretchable nanomembrane sensors and graphene-nanoribbon cell aligners, whose system modulus is matched with target tissues. This multifunctional platform is ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 53 publications
0
71
0
Order By: Relevance
“…Graphene layers on a copper foil are grown using chemical vapor deposition following protocols described in previous reports. [ 35,39 ] A 30 nm Ni layer is deposited onto the Si wafer and, subsequently, 7 nm/70 nm Cr/Au are deposited onto the Ni layer using thermal evaporation. Cr and Au layers are patterned by photolithography and wet etching.…”
Section: Fabrication Of Buckled and Mesh-patterned Cell-sheet-graphenmentioning
confidence: 99%
See 3 more Smart Citations
“…Graphene layers on a copper foil are grown using chemical vapor deposition following protocols described in previous reports. [ 35,39 ] A 30 nm Ni layer is deposited onto the Si wafer and, subsequently, 7 nm/70 nm Cr/Au are deposited onto the Ni layer using thermal evaporation. Cr and Au layers are patterned by photolithography and wet etching.…”
Section: Fabrication Of Buckled and Mesh-patterned Cell-sheet-graphenmentioning
confidence: 99%
“…To prepare cell-sheet-graphene hybrid, C2C12 myoblasts are seeded on the sample with a density of 5 × 10 4 cells cm −2 and cultured by using growth and differentiation media. [ 35 ] The formation of high quality biotic/abiotic interface enables the hybrid to electrically/optically stimulate and effectively monitor the electrophysiological characteristics in vitro and in vivo. Figure S2b, Supporting Information).…”
Section: Fabrication Of Buckled and Mesh-patterned Cell-sheet-graphenmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ceria NPs are known to scavenge ROS and are therefore attractive candidates for inclusion into a graphene-based vehicles or TE platforms. 179 With this in mind, Kim et al 180 recently reported a graphene-based multifunctional platform that can suppress ROS generation. The multifunctional platform was capable of aligning plated cells and in situ monitoring of cellular physiological characteristics during proliferation and differentiation.…”
mentioning
confidence: 99%